Leadership step by step : become the person others follow - Spodek, Joshua (Amacom Books, 2017)
Leadership Step by Step walks readers through what to do and how to do it in an integrated and comprehensive progression of exercises designed to cultivate key abilities, behaviors, and beliefs through experience. The 22 exercises in this hands-on book help you accomplish the inner work and gain the social skills required for great leadership. Each chapter opens with a story demonstrating a leadership skill-and then guides you through the process of developing it.